ROLE OF HMGB1 PROTEIN EXPRESSION IN THE NEONATAL SEPSIS - Orujova, P.A. (World of Medicine and Biology, 2024)
Neonatal sepsis is a significant global health concern, affecting approximately 3 million newborns annually and resulting in up to 375,000 deaths as of 2019. Despite advancements in molecular diagnostics, timely and accurate diagnosis of neonatal sepsis remains a challenge. The high-mobility group box 1 protein, a modulator of immune and metabolic processes, has been identified as a critical player in the pathogenesis of various diseases, including cancer and traumatic shock. This review explores the role of high-mobility group box 1 protein in the pathogenesis of neonatal sepsis, focusing on its secretion mechanisms, its involvement in inflammatory responses, and its potential as a therapeutic target. This role is complex and multifaceted, with studies indicating protective and detrimental effects depending on the context. Understanding high-mobility group box 1 protein՚s function could improve diagnostic markers and targeted therapies, ultimately enhancing outcomes for affected neonates.
Keywords: high-mobility group box 1 protein; neonate; sepsis; inflammation; immunity